Efek Steroid Terhadap Kadar Troponin I dan CRP Pada Pasien Bedah Jantung Koroner di RSUD Arifin Achmad Provinsi Riau - Vera Muharrami (Jurnal Ilmu Kedokteran, 2024)
Steroids can diminish inflammation and forestall cardiac impairment in cardiac surgery cases, encompassing coronary heart surgery; however, this approach remains a topic of ongoing discussion. The present study investigated the ramifications of administering steroids in coronary heart surgery patients, focusing on the variations in CRP and Troponin I level at Arifin Achmad General Hospital in Riau Province. Employing a cross-sectional design, the study retrospectively reviewed medical records of individuals who had undergone coronary heart surgery between January 2018 and September 2020 at Arifin Achmad Hospital in Riau Province. Comparisons between Troponin I and C-Reactive Protein (CRP) levels were drawn contingent on the specific administered steroid (methylprednisolone or dexamethasone). The study further examined secondary outcomes, encompassing myocardial contractility, duration of ventilator employment, and Intensive Care Unit (ICU) length of stay, distinguishing patterns based on the steroid type. Among the 42 analyzed patients, the methylprednisolone and dexamethasone groups exhibited significant increases in troponin I and CRP levels (p<0.05). In contrast, changes in myocardial contractility pre- and post-surgery remained consistent across both groups—similarly, no substantial difference in ventilator or ICU stay duration. As the conclusion, dexamethasone and methylprednisolone have not given any effect in preventing increases in troponin I, CRP levels and myocardial contractility early after coronary heart surgery.